Sex hormone influence on female-biased autoimmune diseases hints at puberty as an important factor in pathogenesis - Yang, Qianfan; Kennicott, Kameron; Zhu, Runqi; Kim, Jooyong; Wakefield, Hunter; Studener, Katelyn; Liang, Yun (Frontiers in Pediatrics, 2023)
The majority of autoimmune diseases affect more women than men, suggesting an important role for sex hormones in regulating immune response. Current research supports this idea, highlighting the importance of sex hormones in both immune and metabolic regulation. Puberty is characterized by drastic changes in sex hormone levels and metabolism. These pubertal changes may be what forms the gulf between men and women in sex bias towards autoimmunity. In this review, a current perspective on pubertal immunometabolic changes and their impact on the pathogenesis of a select group of autoimmune diseases is presented. SLE, RA, JIA, SS, and ATD were focused on in this review for their notable sex bias and prevalence. Due to both the scarcity of pubertal autoimmune data and the differences in mechanism or age-of-onset in juvenile analogues often beginning prior to pubertal changes, data on the connection between the specific adult autoimmune diseases and puberty often relies on sex hormone influence in pathogenesis and established sex differences in immunity that begin during puberty.